Meroplankton seasonal dynamics in the high Arctic fjord: Comparison of different sampling methods. (January 2021) - Weydmann-Zwolicka, Agata; Balazy, Piotr; Kuklinski, Piotr; Søreide, Janne E.; Patuła, Weronika; Ronowicz, Marta
Highlights: Strong seasonality in meroplankton composition found in Isfjorden (high-Arctic) Larvae dynamics was driven mainly by water temperature, photoperiod and algal food Standard WP2 net is an optimal device to collect meroplankton from deeper waters Manually operated suction pump is a good choice in shallow coastal areas The highest meroplankton sampling effort should be undertaken in spring and summer Abstract: Meroplankton comprise mainly of pelagic larvae of benthic invertebrates and play an important role as consumers and prey in coastal ecosystems. During a year-round study in Isfjorden (Svalbard Archipelago; >78°N), two locations (stations North and South) were sampled every third month to capture seasonal dynamics of meroplankton at high-latitudes, using different sampling methods (vertically hauled WP2 plankton net, and SCUBA diver-operated: horizontal towed net and underwater suction pump). Independent of sampling methods, seasonality was the factor that explained the largest part of variation in meroplankton composition (31.8%, PERMANOVA). Distinct seasonal abundance peaks were found of the following taxa: Polychaeta larvae and Cirripedia nauplii in spring; Bivalvia veligers, Echinodermata ophioplutei, and Cirripedia cypris during summer; while Bryozoa cyphonautes in autumn. These changes were driven mainly by water temperature, chlorophyll a concentration, and photoperiod, which according to DistLM routine, jointly explained 36.7% of meroplankton variability. Our results support the theory that planktotrophy is an important larval development strategy in some high Arctic taxa, e.g. Bivalvia and Cirripedia. We also observed that the southern part of Isfjorden was more productive and affected by the advection of Atlantic waters; while the northern location was influenced by the sea ice drift, coming from the north-eastern part of the Isfjord system in winter and spring, and was characterised by higher meroplankton abundances. The comparison of the number of taxa collected by each method and multivariate dispersion index between the standard WP2 plankton net and the remaining devices, operated by SCUBA divers, proved that WP2 is the most optimal method to collect meroplankton, especially from deeper waters. However, an underwater, manually operated suction pump would be a good choice in shallow coastal areas, especially with a dense kelp forest, where using a WP2 net is impossible. The joint use of the WP2 net and suction pump gives the highest value of multivariate dispersion index for the total community, as it additionally allows for the collection of demersal and epibenthic animals which are often omitted by standard net sampling methods, so this combination is worth recommending in studying shallow coastal ecosystems.